Prevalence of non-alcoholic fatty liver disease and its risk factors in patients referred to Ardabil city hospital during 2015-2016 - Zakeri, Anahita; Karamat-Panah, Sepideh (International Journal Of Community Medicine And Public Health, 2018)
Background: Fatty liver is the most common liver disease worldwide, and the number of people with this disease is increasing in the world and in Iran. The aim of this study was to determine the prevalence of non-alcoholic fatty liver disease and its risk factors in patients referred to Ardabil city hospital during 2015-2016. Methods: This is a cross-sectional descriptive study which was done on 80 patients with fatty liver Referred to Ardabil city Hospital dueing 2015-2016. Required information including age, gender, degree of fatty liver, body mass index, serum lipids, liver aminotransferases, serum uric acid, and diabetes mellitus were collected by a cheklist and then analyzed by statistical methods in SPSS.19. Results: 40% of the patients were males and 60% were females. The mean age of the patients was 49.22 ± 14.58 years. 81.2% of the patients were overweight or had some degree of obesity. ALT in 38.5%, AST in 32.5%, ALP in 13.75%, and bilirubin in 21.25% of patients were above their normal range. Total cholesterol in 35%, triglyceride in 50%, and LDL in 17.5% of patients were higher than normal range, and HDL was lower than normal range in 41.2% of patients. 21.25% of patients had hyperuricemia and 38.8% had diabetes. Conclusions: The results showed that non-alcoholic fatty liver is more prevalent in females and older ages. Doing multi-center studies was recommended in Ardabil province or other provinces in Iran in future.